The effectivity of pandanus leaf extract for the treatment of sangkuriang catfish juvenile Clarias gariepinus infected by Aeromonas hydrophila - Siti Sopiah; Rosidah Rosidah; Walim Lili; Iskandar Iskandar; Ibnu Bangkit Suryadi (Jurnal Akuakultur Indonesia)
ABSTRACT